2022
DOI: 10.5171/2022.773904
|View full text |Cite
|
Sign up to set email alerts
|

Tourist Satisfaction Level: Evaluation in a Peruvian Adventure Tour Operator

Abstract: Tourism is an activity that allows economic development by generating employment, promoting cultural manifestations, improving infrastructure, integrating local communities, preserving attractions, and, ultimately, improving people's quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
1
Order By: Relevance
“…It contains the following keywords: Mountain, Adventure, Hiking, Trail, Alpine, Tourism, Area, Mountain Tourism, Landscape, Climbing, Hiker, Bike, Adventure Tourism, Destinations, Mountain Area, Biking, Activity, Management, Natural, and Recreation. The dimensions in this parameter include creating an Adventure Tourism package, assisting in the improvement of product offerings in areas with natural resources [118], analyzing how visitors and tour guides behave in terms of sustainability during Adventure Tourism trips in natural places [119], evaluating the level of customer satisfaction of an adventure trip provider [120], risk management in Adventure Tourism by assisting tourism organizers and adventure tour guides in identifying risk and developing risk mitigation and risk reduction techniques [121], and investigating how Adventure Tourism may help the destination's tourist growth [122].…”
Section: Adventure Tourismmentioning
confidence: 99%
“…It contains the following keywords: Mountain, Adventure, Hiking, Trail, Alpine, Tourism, Area, Mountain Tourism, Landscape, Climbing, Hiker, Bike, Adventure Tourism, Destinations, Mountain Area, Biking, Activity, Management, Natural, and Recreation. The dimensions in this parameter include creating an Adventure Tourism package, assisting in the improvement of product offerings in areas with natural resources [118], analyzing how visitors and tour guides behave in terms of sustainability during Adventure Tourism trips in natural places [119], evaluating the level of customer satisfaction of an adventure trip provider [120], risk management in Adventure Tourism by assisting tourism organizers and adventure tour guides in identifying risk and developing risk mitigation and risk reduction techniques [121], and investigating how Adventure Tourism may help the destination's tourist growth [122].…”
Section: Adventure Tourismmentioning
confidence: 99%
“…It contains the following keywords, Mountain, Adventure, Hiking, Trail, Alpine, Tourism, Area, Mountain Tourism, Landscape, Climbing, Hiker, Bike, Adventure Tourism, Destinations, Mountain Area, Biking, Activity, Management, Natural, and Recreation. The dimension in this parameter include creating an Adventure Tourism package, assisting in the improvement of product offerings in areas with natural resources [106], analyzing how visitors and tour guides behave in terms of sustainability during Adventure Tourism trips in natural places [107], evaluating the level of customer satisfaction of an adventure trip provider [108], risk management in Adventure Tourism by assisting tourism organizers and adventure tour guides in identifying risk and developing risk mitigation and risk reduction techniques [109], and investigating how Adventure Tourism may help the destination's tourist growth [110].…”
Section: 36mentioning
confidence: 99%
“…Therefore, the absence reflects little public interest in entrepreneurial projects. In addition to this, it is important to analyse the frameworks developed by early stage companies in order to develop strategies and educational programs that encourage entrepreneurship (Goyanes, 2015;Cordova-Buiza et al, 2022b;Valencia et al, 2016). From this perspective, Vélez et al (2020) and Friedland &amp Jain (2022) confirmed that entrepreneurship education is related to the development and empowerment of skills, attitudes and values related to entrepreneurship.…”
Section: Literature Reviewmentioning
confidence: 99%